2016
DOI: 10.1177/0961203316655215
|View full text |Cite
|
Sign up to set email alerts
|

Impact of concomitant medication use on belimumab efficacy and safety in patients with systemic lupus erythematosus

Abstract: Practicing physicians have requested efficacy and safety data for belimumab, when used with specific systemic lupus erythematosus (SLE) medications. This was a post hoc analysis of pooled efficacy and safety data from patients who received belimumab 10 mg/kg plus standard of care (SoC) or placebo (SoC) in two Phase III, randomized trials, BLISS-52 and BLISS-76. Patients were categorized into four groups based on baseline concomitant medication usage: steroids only; antimalarials (AM) only; steroids + AM; or st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 14 publications
1
8
0
1
Order By: Relevance
“…[14][15][16] By contrast, hydroxychloroquine seems to have a beneficial effect on damage accrual and long-term prognosis in SLE, 17,18 and the monoclonal antibody belimumab is associated, among other beneficial effects, with steroid sparing. 19,20 In Table 2, the therapy of SLE patients from other observational lupus cohorts is reported, confirming that glucocorticoids are too frequently given to lupus patients across several countries. These data suggest that clinicians should frequently and carefully assess their therapeutic strategies for lupus patients, try to avoid or minimize steroid usage, and take advantage of safer drugs.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…[14][15][16] By contrast, hydroxychloroquine seems to have a beneficial effect on damage accrual and long-term prognosis in SLE, 17,18 and the monoclonal antibody belimumab is associated, among other beneficial effects, with steroid sparing. 19,20 In Table 2, the therapy of SLE patients from other observational lupus cohorts is reported, confirming that glucocorticoids are too frequently given to lupus patients across several countries. These data suggest that clinicians should frequently and carefully assess their therapeutic strategies for lupus patients, try to avoid or minimize steroid usage, and take advantage of safer drugs.…”
Section: Discussionmentioning
confidence: 77%
“…Cardiovascular risk factors and glucocorticoids are both associated with a worse prognosis in lupus patients, being negative factors for long term morbidity and mortality (14)(15)(16). By contrast, hydroxychloroquine seems to have a beneficial effect on damage accrual and long-term prognosis in SLE (17,18), and the monoclonal antibody Belimumab is associated, among other beneficial effects, with steroid sparing (19,20). In table 6 the therapy of SLE patients from other observational lupus cohorts is reported, confirming that glucocorticoids are too much frequently given to lupus patients across several countries.…”
Section: Discussionmentioning
confidence: 99%
“…61 Belimumab has been studied extensively in non-transplant patients with SLE along with concomitant mycophenolate, azathioprine, and steroids and revealed similar safety between those receiving steroids alone and steroids plus anti-malarials. 62 However, in a case report of a patient who continued pre-transplant belimumab along with belatacept after alemtuzumab induction complications including neutropenia, bronchitis, and grade 1a acute cellular rejection occurred. 60…”
Section: Changes To Induction and Maintenance Immunosuppressionmentioning
confidence: 99%
“…A similar study using alemtuzumab along with belimumab in sensitized KT recipients is currently enrolling to evaluate the efficacy and safety of belimumab in preventing the production of de novo donor specific antibodies; however, no results have been reported 61 . Belimumab has been studied extensively in non‐transplant patients with SLE along with concomitant mycophenolate, azathioprine, and steroids and revealed similar safety between those receiving steroids alone and steroids plus anti‐malarials 62 . However, in a case report of a patient who continued pre‐transplant belimumab along with belatacept after alemtuzumab induction complications including neutropenia, bronchitis, and grade 1a acute cellular rejection occurred 60 …”
Section: Agentsmentioning
confidence: 99%
“…van Vollenhoven et al studied the effect of belimumab on corticosteroid dose in SLE patients and found that cumulative corticosteroid dose was substantially smaller than placebo group indicating the belimumab may be steroid sparing [31]. Schwarting et al demonstrated the efficacy and safety of belimumab in combination with standard of care for different grouping of steroid, anti-malarials, and immunosuppressants and observed that overall safety was similar across concomitant medication groups except serious adverse events in the steroids plus antimalarial group [32]. Strand et al have reported the effects of belimumab treatment and standard SLE therapy and found that the disease activity has in fact reduced along with improvement in health related quality of life [33].…”
Section: Clinical Trailsmentioning
confidence: 99%